INTO THE PAST. - White, Rob (Film Quarterly)
The article presents criticism from the editor on the films "Source Code," directed by Duncan Jones, and "Poetry," directed by Lee Chang-dong. He suggests that "Source Code" should have been titled "Lieutenant Stevens Who Can Recall His Past Lives." Lee Chang-dong's previous films "Green History," "Secret Sunshine," and "Peppermint Candy" are also discussed as are his common themes of human trauma and misery.